DYNAMICS OF COMMUNITY COMMUNICATION ARMY IN KEDIRI - Nuriyah, Fitriana Ifa; Ropingi; Ellyda Retpitasari (PT. Antis International Publisher, 2024)
This research was motivated by fans who have excessive and extreme attitudes towards idols, so they enthusiastically control their behavior towards their favorite K-pop idols. This is done by attending meetings and events of local K-pop groups to learn the latest information about the idols they like. The purpose of this study is to explore the process of intrapersonal communication dynamics of Celebrity Worship Syndrome ARMY in Kediri City. The research method used is a qualitative approach and this type of research is a case study. The data collection techniques of this study were conducted through interviews, observation and documentation. The data analysis technique used in this study is an Interactive Model of Analysis, which includes four components, namely data collection, data reduction, data presentation and conclusions. The results of the discussion show that the communication dynamics between the leader of the ARMY group and its members can strengthen their admiration for celebrities by strengthening the importance of BTS as a role model, “home”, pride and consumer behavior. Then, the dynamics of communication between members and ARMY members can strengthen the feeling of admiration for celebrities by building a mutually reinforcing community, influencing the tendency to admire celebrities, using social media, and showing very loyal and faithful behavior toward idols. Then, the dynamics of online communication, namely ARMY's very active, intense, and diverse interaction with K-pop idols through social media, allows them to exchange information, discuss, and share emotions directly with their idols